Gaseous emissions during the solid state fermentation of different wastes for enzyme production at pilot scale. (March 2015) - Maulini-Duran, Caterina; Abraham, Juliana; Rodríguez-Pérez, Sheila; Cerda, Alejandra; Jiménez-Peñalver, Pedro; Gea, Teresa; Barrena, Raquel; Artola, Adriana; Font, Xavier; Sánchez, Antoni
Graphical abstract: Highlights: SSF processes from different wastes were performed for enzyme production. Orange peel + compost, hair and winterization waste with raw sludge were processed. This is the first study where emission factors from SSF processes are given. Hair waste SSF process is characterized by high emission of ammonia. Abundant VOC emission from orange peel treatment is due to the presence of limonene. Abstract: The emissions of volatile organic compounds (VOC), CH4, N2 O and NH3 during the solid state fermentation process of some selected wastes to obtain different enzymes have been determined at pilot scale. Orange peel + compost (OP), hair wastes + raw sludge (HW) and winterization residue + raw sludge (WR) have been processed in duplicate in 50 L reactors to provide emission factors and to identify the different VOC families present in exhaust gaseous emissions. Ammonia emission from HW fermentation (3.2 ± 0.5 kg Mg −1 dry matter) and VOC emission during OP processes (18 ± 6 kg Mg −1 dry matter) should be considered in an industrial application of these processes. Terpenes have been the most emitted VOC family during all the processes although the emission of sulphide molecules during HW SSF is notable. The most emitted compound was dimethyl disulfide in HW and WR processes, and limonene in the SSF of OP.